Non-privileged applicants - Hojnik, Janja (Lex localis, 2009)
In addition to the option of submitting requests for reviewing constitutionality and legality to the Constitutional Court of the Republic of Slovenia, it has been possible for the Slovenian local communities to contest EC. Acts before the EC Courts over the last five years. But the terms and conditions for that are much stricter than those required by the national law. The paper analyses the complex system of legal rules determining the terms and conditions to be observed by local communities to contest the legal acts issued by the EU institutions. These conditions are very strict. They can be hardly fulfilled by local communities because equal conditions apply both to them and to legal / natural persons. For this reason, EU has been criticized for not providing an efficient system of legal remedies to protect the rights of natural and legal persons to whom also local communities pertain. The European Court of Justice partially accepted criticsm, thereby facilitating contestation of EC Acts. However, it limited itself primarily to some specific areas of EC law. Wide criticism of the ECJ has led to some changes being made under the Lisbon Treaty, although these changes are not as liberal as expected.
Keywords: Evropska unija; lokalne skupnosti; Slovenija; Sodišče Evropskih skupnosti; sodna praksa; ustavno pravo